Emerging Semiconductor Technology 1987
DOI: 10.1520/stp25750s
|View full text |Cite
|
Sign up to set email alerts
|

The Bonding Structure and Compositional Analysis of Plasma Enhanced and Low Pressure Chemical Vapor Deposited Silicon Dielectric Films

Abstract: Silicon dielectric films such as silicon nitride, oxide and oxynitride films deposited by Plasma Enhanced and Low Pressure Chemical Vapor Deposition (PECVD and LPCVD) processes were analyzed and compared using Fourier Transform Infrared (FTIR), X-ray Photoelectron, Auger, Electron Spin Resonance Spectroscopies and Nuclear Reaction Analysis for hydrogen. The plasma deposited films exhibit a more random structure with less long-range order and contain more hydrogen as compared to those of LPCVD films. However, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1989
1989
2004
2004

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Table II shows the half-peak width comparison between ECR, thermal and plasma deposited nitride and oxide films. The FTIR spectra of both plasma and thermal silicon nitride and oxide films, used for comparison with ECR plasma-deposited films in this study, have appeared in recent publications (9)(10)(11)(12). The vibrational bands halfpeak width of the Si--N (880 cm -1) and Si--O (1065 cm -1) modes of the plasma films are normally broader, while those of ECR and thermal films are about the same.…”
Section: Resultsmentioning
confidence: 99%
“…Table II shows the half-peak width comparison between ECR, thermal and plasma deposited nitride and oxide films. The FTIR spectra of both plasma and thermal silicon nitride and oxide films, used for comparison with ECR plasma-deposited films in this study, have appeared in recent publications (9)(10)(11)(12). The vibrational bands halfpeak width of the Si--N (880 cm -1) and Si--O (1065 cm -1) modes of the plasma films are normally broader, while those of ECR and thermal films are about the same.…”
Section: Resultsmentioning
confidence: 99%
“…IR has been utilized for the comparison of films deposited by different deposition techniques [65]. In this publication, the films deposited by LPCVD showed a broad band as a combination of overlapping bands with various small maxima resulting from the Si-O and Si-N vibrations in the possible N-Si-O bonding environments, while the PECVD spectra showed wider absorption bands with less distinguishable Si-O and Si-N bands because of the more random bonding structure and the higher concentration of hydrogen.…”
Section: Infrared Spectrometrymentioning
confidence: 99%
“…Electron spin density measurements for unpaired electrons in [65] showed that films with a refractive index of 1.75-1.78 had the lowest spin density. The films were 1-2 µm thick and deposited on silicon substrates.…”
Section: Electron Spin Resonancementioning
confidence: 99%
See 2 more Smart Citations